SOSIALISASI UMKM NAIK KELAS INOVASI DAN KOLABORASI MENUJU PASAR GLOBAL DESA BABAKAN LOR KECAMATAN CIKEDAL KABUOATEN PANDEGLANG - Husni, Mohamad; Azlansyah, Muhammad Noor; Astuti, Angggun Wahyu Dwi; Putri, Nabila Herlina; Wibowo, Aben Tri; Sumarni, Jelia; Salma, Qanitah; Naman, Naman; Maulana, Aqmal (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2025)
This community service activity was carried out in Babakan Lor Village, Cikedal District, Pandeglang Regency, with the aim of enhancing the capacity of MSME actors in facing global market challenges. The main focus is on the development of local flagship products, namely coconut pudding and emping, through an approach of innovation and collaboration. The socialization and training provided include enhancing understanding of the importance of product innovation, digital marketing strategies, modern packaging, and business legality as prerequisites for entering the export market. The results of the activities show an increase in knowledge, motivation, and collaborative spirit among MSME actors, marked by the formation of working groups and follow-up plans. This activity proves that education-based empowerment and multi-party synergy can be an effective strategy in encouraging village SMEs to level up and become competitive on a global scale.